2015
DOI: 10.1002/lary.25248
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of satellite cells activity and MyoD in rat thyroarytenoid muscle after reinnervation

Abstract: These data suggested that NMJ formation following reinnervation might prompt recovery of M-cadherin and MyoD mRNA expression to the quiescent level of SCs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 36 publications
0
8
0
Order By: Relevance
“…SCs are generally located between the plasma membrane and surrounding basal lamina. SCs are mostly quiescent under normal conditions, but are activated in response to mechanical stress or denervation, leading to their proliferation and differentiation to form new myofibers . Pax7 and MyoD are the main transcription factors regulating SC fate.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…SCs are generally located between the plasma membrane and surrounding basal lamina. SCs are mostly quiescent under normal conditions, but are activated in response to mechanical stress or denervation, leading to their proliferation and differentiation to form new myofibers . Pax7 and MyoD are the main transcription factors regulating SC fate.…”
Section: Discussionmentioning
confidence: 99%
“…The effects of bFGF injection into human vocal folds have already been reported without risks of granulation formation or carcinogenesis . Considering that RLN denervation induces SC activation and proliferation, and the effects decrease gradually, future studies would be necessary to determine the optimal timing for bFGF administration and its long‐term effects.…”
Section: Discussionmentioning
confidence: 99%
“…Kodama et al found significant increases in muscle transcription factors MyoD and M‐cadherin in denervated rat thyroarytenoid muscle, which return to baseline after nerve recovery . These factors activate native MPCs and stimulate their proliferation.…”
Section: Discussionmentioning
confidence: 97%
“…Kodama et al found significant increases in muscle transcription factors MyoD and M-cadherin in denervated rat thyroarytenoid muscle, which return to baseline after nerve recovery. 16 These factors activate native MPCs and stimulate their proliferation. Cultured MPCs added to the denervated muscle would be expected to respond similarly to these transcription factors, as apparently occurred in these experiments.…”
Section: Discussionmentioning
confidence: 99%
“…Glottal closure in the elderly can be mostly incomplete due to atrophic changes of the TA muscle with aging, especially in men . Atrophy of the vocal cords in the elderly results from the scarcity of elastic fibers and hyaluronic acid, and combined with atrophy of the vocal cord muscles could affect phonation . A cross‐innervation pattern to the TA muscle via the external branch of the superior laryngeal nerve and the classical recurrent laryngeal nerve further increases the challenge of understanding and treating dysfunction of the TA muscle .…”
Section: Discussionmentioning
confidence: 99%